The Influence Of Macroeconomic Factors And World Commodity Prices On The Volatility Of The Indonesian Sharia Stock Index - Agus Afrianingsih, Dwi; Yunita, Irni (Publisher Cv. Inara, 2025)
The Indonesia Sharia Stock Index (ISSI) serves as a key indicator of sharia-compliant stock performance on the Indonesia Stock Exchange. This study investigates the impact of macroeconomic factors—interest rates, exchange rates, inflation, oil prices, and gold prices—on ISSI volatility from January 2015 to December 2024. Utilizing a quantitative approach with multiple regression analysis, the findings reveal that interest rates significantly negatively affect volatility (coefficient -0.509, significance 0.001), indicating that higher interest rates reduce market volatility. In contrast, the exchange rate and inflation show no significant effects (coefficients -0.308 and 0.144). World oil prices have a marginal negative impact (coefficient -0.200), while gold prices are not significant (coefficient 0.045). ANOVA results confirm that all independent variables collectively influence ISSI volatility significantly (significance 0.005). This research underscores the importance of macroeconomic factors in investment decision-making within the sharia market and suggests future studies incorporate sectoral analysis and additional control variables for deeper insights.